Readability analysis of teaching materials of English courses class 2 and 6 elementary school - Sinta Dewi; Nuryansyah Adijaya (Mitra Palupi, 2022)
Background: Textbooks are one of the learning media used by elementary school students. Textbooks function to support teachers in the learning process and become a source of knowledge for students in following the learning process. Books as teaching materials are books that contain various subject matter produced by an author based on the applicable curriculum and serve as guidelines for teachers and students in the learning process. Purpose: This study focuses on the study to describe the level of readability of teaching materials adapted to children's cognition. Design and methods: The method used is a qualitative method with data analysis of readability text on webfx . The data used as a source in this study is in the form of text contained in teaching materials for English lessons for grades 2 and 6.. Results: Based on the results of the readability text on webfx , only a book with the title Knowing Kinds of Animals Using the Game